Clean perversion in consumer culture - Prado, José Luiz Aidar (MATRIZes, 2019)
Contemporary culture is a perverse assembly, as it seeks to liberate the selfish subject to the world of the sensitive and the drive. In the 20th century an increasing liberation of the drives occurred, connecting the neurotic consumer and the puritan perverse. The perversion is sought, but remaining clean, demanding strong musical beatings and varied substances varying between the postmodern neurotic consumer and the puritan perverse to this end. The result is a society in which everyone internalizes the law of the market to satisfy the drives, disconnecting the subject function. To understand the transformations of communication culture of the perverse city, a psychoanalytic theory of the drives and passions is necessary.